Photophysical behavior of new acridine(1,8)dione dyes - Cabanzo Hernández, Rafael (2013)
The photophysical behavior of five acridine(1,8)dione dyes of biological interest was studied by absorption and fluorescence spectroscopy, photoacoustics and time resolved phosphorescence techniques. The results obtained in ethanol and acetonitrile solutions show that the main spectroscopic and photophysical parameters of these compounds depend strongly on both the solvent and oxygen concentrations. Oxygen completely quenched the triplet state of all dyes. In nitrogen-saturated solutions, quantum efficiencies of triplet formation in ethanol were lower than those in acetonitrile